2016
DOI: 10.1177/0013161x16651926
|View full text |Cite
|
Sign up to set email alerts
|

Can Professional Development Improve School Leadership? Results From a Randomized Control Trial Assessing the Impact of McREL’s Balanced Leadership Program on Principals in Rural Michigan Schools

Abstract: Purpose: This multiyear experimental study was designed to examine (1) the causal impact of McREL International's Balanced Leadership® Professional Development (BLPD) program on school principals' learning, beliefs, and behaviors and (2) whether there were differences in the types of outcomes the professional development influenced. Outcomes included principals' reported sense of efficacy, perceptions of school climate, and leadership behaviors. Research Methods: Approximately 100 school principals in rural Mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 31 publications
(51 reference statements)
1
19
0
4
Order By: Relevance
“…Leithwood and Jantzi (2008) suggest that leaders empower the more effective teachers and that it is through them that their student learning is experienced. More recent research has shown that professional development for school leaders is key to their development and can result in improved student learning outcomes (Miller et al, 2016;Grissom et al, 2021).…”
Section: School Leadership In Lics and Micsmentioning
confidence: 99%
“…Leithwood and Jantzi (2008) suggest that leaders empower the more effective teachers and that it is through them that their student learning is experienced. More recent research has shown that professional development for school leaders is key to their development and can result in improved student learning outcomes (Miller et al, 2016;Grissom et al, 2021).…”
Section: School Leadership In Lics and Micsmentioning
confidence: 99%
“…The program consists of 10 2-day workshops focused on 21 leadership functions, carried out over a 2-year period. Principals in the program apply learning between sessions and reflect on application with other principals and trainers (Miller et al, 2016).…”
Section: The Principal Development Pipelinementioning
confidence: 99%
“…quasi-experimentellem Design unterstützt (vgl. Jacob, Goddard, Kim, Miller & Goddard, 2015;Miller, Goddard, Kim, Jacob, Goddard & Schroeder, 2016;Petridou, Nicolaidou & Karagiorgi, 2017). Die Teilnehmer*innen der jeweiligen Treatment-Gruppen berichteten in diesen Untersuchungen über positive Veränderungen verschiedener Einstellungsmerkmale (z.…”
Section: Berufl Iches Lernen In Fortbildungenunclassified